ON THE PLACE OF SOUTH CAUCASUS IN THE CONTEXT OF SOVIET - PERSIAN RELATIONS IN 1917-1921 - Tamara Bulygina; Karine Ambartsumyan (Гуманитарные и юридические исследования)
The article studies the problem of evolution of Soviet -Persian relations. With the reference to a complex of published and archival sources, the authors reveal the main stage of development of these relations when Persia was changing its status from the sphere of influence into a partner. South Caucasus played an important role in the process. The starting point of the research is the October 1917 coup, the upper chronological frame is defined as 1921, when the Soviet-Iranian treaty was concluded. In the first part of the article, a review of relation between Russian SFSR and Persian government is given. The authors found out that until 1920 the policies of the Persian government, including in relation to the Bolsheviks, were determined by the British. During this period, South Caucasus and Persia came under the complete control of Britain. Sovietization of Azerbaijan determined the beginning of a new stage in the development of the eastern policy of Bolshevik's government. At that time the idea of exporting revolution to the East predominated among Soviet leaders. Soviet Azerbaijan became a springboard to influence the Kuchuk Khan insurgent movement in Gilan. The signing of the treaty in 1921 had become a factor in enhancing the significance of the South Caucasus. First, the region played an important role in establishing trade exchange between Persia and Russia. Using complex archival documents the authors reconstructs process of setting up economic relations. With specific historical examples they shows how in the process of building Soviet-Persian interaction, South Caucasus became more and more involved in the sphere of Russian influence. It was determined that during the period under investigation the region played an integrative role. This circumstance is especially noteworthy when referring to an earlier historical past, when in the XIX century Caucasus was the area of Russian-Iranian confrontation.